When two-pizza teams plan a banquet : lightweight architecture governance (O'Reilly Media, 2019)
"Jonny LeRoy explores the Goldilocks zone that makes sure organizational risks and opportunities are handled while still giving teams as much autonomy as possible within those constraints. He draws on ThoughtWorks's recent client experience to delve into some of the strategies and approaches for creating the Goldilocks zone of lightweight governance: automating compliance, focusing on vision, principles and constraints, enrolling gatekeepers as collaborators, paved roads and the pit of success, tech radar as a lightweight governance tool, and ADRs for visibility. He also touches on how to help architects become comfortable with evolution, the org design implications, how to be responsive to skill levels on teams, and how to think about innovation zones."--Resource description page